Analisis Faktor-Faktor yang Mempengaruhi Disparitas Indeks Pembangunan Manusia antara Kota Banjarmasin dan Kota Banjarbaru Tahun 2010-2019 - Muhammad Zakkie; Muhammad Effendi (PPJP Universitas Lambung Mangkurat, 2022)
This study aims to determine which factors have the most dominant influence on HDI disparities. The analysis used is the two independent sample difference test, namely to determine the condition of the HDI disparity between Banjarmasin City and Banjarbaru City and also uses multiple linear regression analysis to determine the effect of economic growth, employment opportunities, and poverty on HDI disparity and also to determine the most significant factors. dominantly affects the HDI disparity..Based on the research results, it shows that the HDI of the cities of Banjarmasin and Banjarbaru has always increased every year, thus human development in the cities of Banjarmasin and Banjarbaru is quite good, which means that in general the quality of education and health services is getting better. However, based on the results of multiple linear regression analysis, only the poverty variable has a significant effect, while economic growth and job opportunities from both the city of Banjarmasin and the city of Banjarbaru do not have a significant effect on HDI, this happens because the purchasing power index of the city is insufficient, causing inequality. and also in large employment opportunities are more filled by outsiders or migrants, so that the job opportunities available do not affect job opportunities in the city.